A study on the relationship between psychological capital, organizational identification, and job burnout among university teachers - Mingmei, Yang; Pek, Lim Seong (Intelektual Pustaka Media Utama, 2024)
To gain a comprehensive understanding of job burnout among Chinese university teachers, this study examined the impact of teachers' psychological capital on job burnout from the perspective of organizational identification. A survey was conducted among 350 teachers from five colleges and universities in Henan Province of China using a convenient sampling method. Data were analyzed using SPSS23.0 and process macros. The findings revealed that while teachers' psychological capital and organizational identification are generally high, there is a moderate level of job burnout. Furthermore, there was a substantial positive link found between teachers' psychological capital and organizational identification, with psychological capital significantly predicting organizational identification. Both psychological capital and organizational identification demonstrated significant negative correlations with job burnout, plus substantial predictive effects. Mediation analysis suggested that organizational identification partially mediates the relationship between teachers' psychological capital and job burnout.